Answer:
Option (d)
Step-by-step explanation:
Given,
y" +y=sin x ...........(1)
The particular solution
[tex]y_p=A x sinx +Bx cosx[/tex]
[tex]y'_p=Axcosx+Asinx+B cosx-Bxsinx[/tex]
[tex]y"_p=Acosx-Axsinx+Acosx-Bsinx-Bsinx-Bxcosx[/tex]
[tex]y"_p=2Acosx-Axsinx-2Bsinx-Bxcosx[/tex]
Putting the value of y" and y in equation (1)
[tex]2Acosx-Axsinx-2Bsinx-Bxcosx+Axsinx+Bxcosx = sinx[/tex]
[tex]\Rightarrow 2Acosx-2Bsinx=sinx[/tex]
Therefore 2A =0 -2B=1
⇒A=0 [tex]\rightarrow B=-\frac{1}{2}[/tex]
Therefore [tex]y_p=-\frac{1}{2} x cosx[/tex]